Tropologia w hermeneutyce Hieronima ze Strydonu - Nowaszczuk, Jarosław (Vox Patrum, 2024)
Tropology is one of the patristic methods of interpreting the biblical text. Saint Jerome includes it in his hermeneutical canon, which he calls "the triple description and rule of Sacred Scripture" (triplex descriptio et regula Scripturarum). He also explains that the essence of tropology is moral interpretation. The main problem of this study is to present the provenance of this method, and then to discuss what it consists of in the understanding of Saint Jerome and what rules it is governed by.